1992
DOI: 10.1002/jbm.820260711
|View full text |Cite
|
Sign up to set email alerts
|

Agarose for a bioartificial pancreas

Abstract: Islets were encapsulated into 5% concentration agarose microbeads. The effect of microencapsulation on islet allograft survivals was determined using a streptozotocin-induced diabetic (STZ) mouse and a nonobese diabetic (NOD) mouse as recipients. All five STZ BALB/c mice receiving microencapsulated islets (C57BL/6) maintained normoglycemia indefinitely. When NOD mice were used as recipients of the bioartificial pancreas, four of five grafts (islets from C3H/He) functioned for more than 80 d. Two of five NOD mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(81 citation statements)
references
References 15 publications
0
81
0
Order By: Relevance
“…In diabetic canine recipients, these devices demonstrated a 50 % success rate in achieving insulin independence for 7-12 week period, demonstrating efficacy in large animal models [49]. Subcutaneously implanted hollow fiber implants demonstrated better glycemic control, minimal fibrotic response and better protection from the immune system when they were manufactured with smooth outer surfaces compared to implants with rough or fenestrated outer surfaces [50][51][52][53]. Prevost et al [54] reported that AN69 hollow fiber implants containing syngeneic islets demonstrated euglycemia for a 10 week period after transplantation into STZ-induced diabetic rats.…”
Section: Tubular Devicesmentioning
confidence: 99%
“…In diabetic canine recipients, these devices demonstrated a 50 % success rate in achieving insulin independence for 7-12 week period, demonstrating efficacy in large animal models [49]. Subcutaneously implanted hollow fiber implants demonstrated better glycemic control, minimal fibrotic response and better protection from the immune system when they were manufactured with smooth outer surfaces compared to implants with rough or fenestrated outer surfaces [50][51][52][53]. Prevost et al [54] reported that AN69 hollow fiber implants containing syngeneic islets demonstrated euglycemia for a 10 week period after transplantation into STZ-induced diabetic rats.…”
Section: Tubular Devicesmentioning
confidence: 99%
“…Microencapsulation can be achieved via the formation of a gel shell around the islets by polymerization of a precursor solution around islet surfaces. Emulsification is one of the microbead formation methods (Iwata et al, 1992;Yang et al, 1994). PEG/Alginate was used for islets microencapsulation through their mixing with two-phase aqueous emulsion.…”
Section: Macro and Microencapsulationmentioning
confidence: 99%
“…In most cases, smooth round surfaces had the lowest fibrosis promoting effect (Zhang et al, 2008). The most commonly applied materials for microencapsulation are alginate (Lim et al, 1980), agarose (Iwata et al, 1992), PEG and poly(hydroxyethylmetacrylate-methyl methacrylate) (Dawson et al, 1987).…”
Section: Macro and Microencapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of agarose microcapsules for cell therapy has been demonstrated by both allo-transplantation and xeno-transplantation of pancreatic islets. [8][9][10] The general method for preparing cell-enclosing agarose microcapsules is based on water-in-oil emulsion, which is followed by a reduction in the temperature to allow gellation of the agarose droplets. In general, the agarose droplets are produced by dispersion of agarose aqueous solution-in-oil via mechanical stirring or shaking.…”
Section: Introductionmentioning
confidence: 99%